Advances in the structure and function of the nucleolar protein fibrillarin - Zhang, Xue; Li, Wenxin; Sun, Shulan; Liu, Yefu (Frontiers in Cell and Developmental Biology, 2024)
Fibrillarin (FBL) is a highly conserved and well-researched nucleolar protein found in eukaryotes. Its presence was first identified in 1985 through protein immunoblotting analyses using antisera from patients with autoimmune scleroderma. Through immunoelectron microscopy, FBL was shown to be localized in the dense fibrillar component of the nucleolus, leading to the term “fibrillarin”. The FBL protein is composed of 321 amino acids and contains two significant functional domains: the GAR domain and the methyltransferase domain. It is expressed in the nucleolus of eukaryotes. This makes FBL one of the most studied nucleolar proteins. While methylation is not essential for cell survival, the FBL gene is crucial for eukaryotic cells, underscoring the importance of investigating additional functions that do not rely on FBL methylation. This review will primarily examine the protein structural domains of FBL and its classic methyltransferase activity. Additionally, our review will examine the importance of the eukaryote-specific GAR structural domain of FBL in regulating intracellular phase separation. Furthermore, this paper analyzes recent developments in the utilization of FBL in the study of pathogen infections and cancer research over the past decade.